2020
DOI: 10.1155/2020/4710527
|View full text |Cite
|
Sign up to set email alerts
|

Tai Chi Chuan for Subjective Sleep Quality: A Systematic Review and Meta‐Analysis of Randomized Controlled Trials

Abstract: Background. This review aims to investigate the efficacy of Tai Chi Chuan on subjective sleep quality among adults. Methods. We systematically searched PubMed, Embase, Cochrane Library, Scopus, CNKI (China National Knowledge Infrastructure), and the Wanfang Database from their inception to August 2019 and identified 25 eligible studies that were published in both English and Chinese. Results. 24 out of 25 studies were identified to be high-quality studies according to the PEDro scale. The pooled results confir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 78 publications
(201 reference statements)
0
16
0
Order By: Relevance
“…In 2010, Wang and coworkers, in their systematic review, documented the effects of Tai Chi on improvement in psychological well‐being, including mood, decreased stress, and anxiety 65 . Two recently published systematic reviews with meta‐analyses have reported sleep quality improvement via Tai Chi training 66,67 …”
Section: Non‐pharmacologic Therapiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2010, Wang and coworkers, in their systematic review, documented the effects of Tai Chi on improvement in psychological well‐being, including mood, decreased stress, and anxiety 65 . Two recently published systematic reviews with meta‐analyses have reported sleep quality improvement via Tai Chi training 66,67 …”
Section: Non‐pharmacologic Therapiesmentioning
confidence: 99%
“…Chi training. 66,67 Yoga, in its ancient spiritual concept, originated in the Indian subcontinent more than 5000 years ago, comprises meditation, breathing exercises, lifestyle advice, and body positions. The Western version, known as "modern postural yoga" consists mainly of postures usually connected by flowing sequences.…”
Section: Exercisementioning
confidence: 99%
“…For healthy adults, there were moderate improvements in sleep quality (low certainty) and small improvements for adults with chronic diseases (low certainty) [85]. Two of the three RCTs in the meta-analysis of sleep quality for cancer survivors (very low certainty, equivalent effect) [82] overlapped with the this larger meta-analysis of 15 RCTs for adults with chronic diseases [85].…”
Section: Cognitive Function and Impairmentmentioning
confidence: 95%
“…Twenty of the other SRs included in the evidence synthesis also reported AEs (Table 2). Of which, 18 reported no AEs [61,69,71,75,80,82,83,85,88,89,92,93,[95][96][97][102][103][104] and two reported mild, transient musculoskeletal AEs [81,84].…”
Section: Adverse Eventsmentioning
confidence: 99%
“…50 Two recently published systematic reviews with meta-analyses have reported sleep quality improvement via Tai Chi training. 51,52 Yoga , in its ancient spiritual concept, originated in the Indian subcontinent more than 5.000 years ago, comprises meditation, breathing exercises, lifestyle advice, and body positions. The Western version, known as 'modern postural yoga' consists mainly of postures usually connected by flowing sequences.…”
Section: Exercisementioning
confidence: 99%